A Multivariable Submersible Sensor for Monitoring in Real-Time Industrial Flotation Cells - Artigas-Abuin, A; Maldonado-Saavedra, M (Elsevier Ltd, 2024)
This paper describes the development and validation of a submersible sensing technology for industrial flotation cells. The sensor provides simultaneous real-time measurements of gas and solid holdups, as well as the density and viscosity of the slurry in the pulp zone of flotation machines. The submersible device comprises a gas exclusion cell, which resembles an inverted truncated cone assembled to a single-straight tube Coriolis meter. When the sensor device is vertically immersed in the aerated slurry, a continuous bubble-free flow of slurry is induced through the device, which allows the Coriolis meter to provide measurements of the slurry flow, density, and viscosity. The magnitude of the induced flow is a primary function of the sensor s geometry and gas holdup. Applying the Bernoulli equation reveals that gas holdup can be expressed as the square of the induced flow velocity. A discharge coefficient parameter is introduced to compensate for variations in the velocity profile and flow losses. This coefficient is a function of the fluid Reynolds number, calculated in real-time based on the Coriolis measurements. The sensing technology was assessed in a pilot column operated in a water–air system and industrial forced-air and self-aspirated large flotation cells. Results demonstrate the sensor s capabilities to provide reliable, accurate, real-time, long-term continuous gas dispersion and solid suspension-related variables, which could be used for supervision, control, and optimization applications. © 2024 Elsevier Ltd